2020
DOI: 10.2320/matertrans.mt-mn2019005
|View full text |Cite
|
Sign up to set email alerts
|

Development of NH<sub>3</sub> Gas Sensors at Room Temperature Based on Modified Carbon Nanotubes

Abstract: Multiwalled carbon nanotubes (CNTs) were modified with the Hummers method and coated onto Pt electrodes patterned on SiO 2 /Si(001) surface to fabricate chemical sensors. The modified CNTs showed a different structure and increased number of defects compared with pristine CNTs, these properties facilitated the adsorption of NH 3 gas molecules on the CNT surfaces. NH 3 gas sensing results indicate that the sensor exhibited an enhanced response to gas at room temperature. The response of the modified CNT-based s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…5. In the third paper, 183) development of gas sensors for the NH 3 using the carbon nanotubes is shown, in which multiwalled carbon nanotubes (CNTs) were coated onto Pt electrodes patterned on SiO 2 /Si(001) surface. The fourth paper 184) reports preparations of natural rubber-based electromagnetic shielding materials for coating application, in which expanded graphite was prepared and dispersed in the polyaniline/natural rubber matrix.…”
Section: Carbon and Organic Materialsmentioning
confidence: 99%
“…5. In the third paper, 183) development of gas sensors for the NH 3 using the carbon nanotubes is shown, in which multiwalled carbon nanotubes (CNTs) were coated onto Pt electrodes patterned on SiO 2 /Si(001) surface. The fourth paper 184) reports preparations of natural rubber-based electromagnetic shielding materials for coating application, in which expanded graphite was prepared and dispersed in the polyaniline/natural rubber matrix.…”
Section: Carbon and Organic Materialsmentioning
confidence: 99%
“…Signicant research on the detection of NH 3 using CNT-based chemiresistive sensors has been performed. [149][150][151][152][153][154] In one of the studies, Ansari et al observed that SWCNTs functionalized using nitric acid (f-SWCNTs) showed a higher response than pristine SWCNTs 153 together with a long recovery time due to the strong chemical bonding of the gas molecules with the functional groups of SWCNTs. In another work, Schütt and coworkers synthesized tetrapodal ZnO networks (ZnO-T) decorated with MWCNTs as an NH 3 sensing material.…”
Section: Nh 3 Sensorsmentioning
confidence: 99%
“…32,33,[35][36][37] Additionally, it can detect NH 3 , which is typically difficult to detect using the metal oxide gas sensors. 38,39 Single-walled CNTs (SWCNTs) exhibit metallic and semiconducting electrical properties depending on the chirality of the cylindrically wrapped graphene sheet. 40 The metallic and semiconducting SWCNTs were mixed in the synthesized mixture in a ratio of 1:2 based on the chirality-based analysis.…”
mentioning
confidence: 99%